Covariant hodograph transformations between nonlocal short pulse models and the AKNS(−1) system. (February 2019) - Chen, Kui; Liu, Shimin; Zhang, Da-jun
Abstract: The paper presents hodograph transformations between nonlocal short pulse models and the first member in the Ablowitz–Kaup–Newell–Segur negative hierarchy (AKNS( − 1 )). Multi-component cases are also considered. It is shown that the independent variables of the short pulse models and AKNS( − 1 ) that are connected via hodograph transformations are covariant in nonlocal reductions.